Ecdysteroid Titer and Metabolism and cuticle deposition during embryogenesis of the ixodid tick amblyomma-hebraeum (Koch) - Dotson, Ellen Marie; Connat, Jean-Louis; Diehl, Peter-Allan (My University, 1995)
Three embryonic cuticles are formed before larval cuticle deposition during embryonic development of Amblyomma hebraeum. The quantity of radioimmunoassay-positive material varied between 50 and 200 pg ecdysone equivalents per mg, but no significant peaks were detected. Maternally incorporated [H-3]-20-hydroxyecdysone and [H-3]-ecdysone contained in freshly laid eggs appear to be conjugated to C-22 fatty acid esters and 3 alpha epimers of those esters and, thus, appear doubly inactivated. In addition, ecdysone is converted to an unknown product called 2'. The role of these maternally derived ecdysteroids is unknown.
Keywords: AMBLYOMMA HEBRAEUM; APOLAR CONJUGATES; CUTICLE DEVELOPMENT; ECDYSTEROIDS; ECDYSTEROID METABOLISM; 3-ALPHA ECDYSTEROIDS; EMBRYONIC; CUTICLES; EPIMER; TICK; ORNITHODOROS-MOUBATA MURRAY; INTEGUMENT STRUCTURE; BOOPHILUS-MICROPLUS; SENSU WALTON; IXODOIDEA; ECDYSONE; TITERS; EGGS; ARGASIDAE; ACCUMULATION